"My Reality is Just Different From Yours, That Doesn't Mean I'm Crazy." Exploring the Impact of Childhood Emotional Abuse on Adult Emotional Adjustment. Issue 1 (2nd January 2020) - Newton, Claira; Gavin, Helen
ABSTRACT: Childhood emotional abuse (CEA) is a pervasive set of destructive behaviors that has negative effects lasting into adulthood. In order to examine these negative effects, it is important to determine the links between CEA and adult adjustment, i.e., how various forms of abuse are dealt with by the recipients, and how effective different coping strategies are. A small-scale online survey was developed that included questions designed to elicit both qualitative and quantitative data, to facilitate the collection of rich and useful data, while maintaining participant anonymity. The survey was disseminated via social media and a number of charitable organizations working with adult victims of child abuse. Using qualitative and quantitative analytical procedures, research findings suggested how childhood experiences of emotional abuse impact on adulthood. The findings also exposed a potentially effective coping strategy that could be incorporated into practice settings. The identified coping strategy, reading was reported as effective when employed in both childhood and adulthood and may help clients cope with abusive experiences.